Development of catalytic materials for decomposition of ADN-based monopropellants. (May 2019) - Maleix, Corentin; Chabernaud, Pierre; Brahmi, Rachid; Beauchet, Romain; Batonneau, Yann; Kappenstein, Charles; Schwentenwein, Martin; Koopmans, Robert-Jan; Schuh, Sebastian; Scharlemann, Carsten
Abstract: Hydrazine (N2 H4 ), one of the widest used liquid monopropellant is to be replaced by "greener" propellants based on ammonium dinitramide (ADN, NH4 + N(NO2 )2 - ), such as LMP-103S and FLP-106 within the framework of the Horizon 2020 Rheform project. While hydrazine can rely on a catalytic technology based on conventional materials such as γ-Al2 O3 (due to the adiabatic decomposition temperature of about 900–1000 °C), LMP-103S and FLP-106 require catalyst support materials that can withstand higher temperatures (about 1650 °C and 1900 °C, respectively) and exhibit a sufficient porosity and resistance to sintering. On these terms, among the various candidates for catalyst support, monolith-shaped supports were investigated. Highlights: Ammonium DiNitramide (ADN) investigated in the form of two liquid propellants blends, namely FLP-106 and LMP-103S. Several catalysts shapes investigated: granulated catalysts and monolithic catalysts. 3D printing of complex ceramic structures investigated towards a washcoating process. Decomposition tests of FLP-106 and LMP-103S after impregnation of potential active metal solutions. Textural behaviour of the washcoat layer studied after several heat treatments up to 1500 °C for different durations.